2020
DOI: 10.1101/2020.09.17.20196352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The epidemiological characteristics of COVID-19 in Libya during the ongoing-armed conflict

Abstract: Introduction: COVID-19 can have even more dire consequences in countries with ongoing armed conflict. Libya, the second largest African country, has been involved in a major conflict since 2011. This study analyzed the epidemiological situation of the COVID-19 pandemic in Libya, examined the impact of the armed conflict in Libya on the spread of the pandemic, and proposes strategies for dealing with the pandemic during this conflict. Methods: We collected the available information on all COVID-19 cases in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…The copyright holder has placed this this version posted February 16, 2021. ; https://doi.org/10.1101/2021.02.12.21251654 doi: medRxiv preprint Our data indicate that the armed-conflict has masked the actual status of the epidemic at an early stage. This is in concordance with previous data published by Daw et al, which showed that the ongoing-armed armed conflict in these volatile regions has influenced the spread of the pandemic either by masking the actual prevalence in the armed controlling areas and accelerating the spread of the pandemic in the non-controlled region ( 23).…”
Section: Discussionsupporting
confidence: 93%
“…The copyright holder has placed this this version posted February 16, 2021. ; https://doi.org/10.1101/2021.02.12.21251654 doi: medRxiv preprint Our data indicate that the armed-conflict has masked the actual status of the epidemic at an early stage. This is in concordance with previous data published by Daw et al, which showed that the ongoing-armed armed conflict in these volatile regions has influenced the spread of the pandemic either by masking the actual prevalence in the armed controlling areas and accelerating the spread of the pandemic in the non-controlled region ( 23).…”
Section: Discussionsupporting
confidence: 93%